DOI: 10.31274/etd-180810-3843
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heat stress on energetic metabolism and insulin homeostasis

Abstract: Proper insulin homeostasis appears critical for adapting to and surviving a heat load. Further, heat stress (HS) induces phenotypic changes in livestock that suggest an increase in insulin action. The current study objective was to evaluate the effects of HS on whole-body insulin sensitivity. Female pigs (57±4 kg body weight) were subjected to two experimental periods. During period 1, all pigs remained in thermoneutral conditions (TN; 21°C) and were HEC remained similar in HS pigs while it decreased (36%) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 221 publications
(438 reference statements)
0
5
0
Order By: Relevance
“…Two studies (dated 1988, Pedrosa & Sanz, 1993, 1997 Table 3. Regional employment dependent on automotive plants.…”
Section: An Estimate Of the Economic Significance Of The Volkswagen Nmentioning
confidence: 99%
“…Two studies (dated 1988, Pedrosa & Sanz, 1993, 1997 Table 3. Regional employment dependent on automotive plants.…”
Section: An Estimate Of the Economic Significance Of The Volkswagen Nmentioning
confidence: 99%
“…In the following, we determine this function for the Langmuir FEBID model under equilibrium conditions. 45 Using the compact notation based on the characteristic FEBID frequencies that we previously developed, 48 the dynamics of fractional surface molecule coverage under no diffusion θ can be described as a competition be-tween the characteristic frequencies of gas adsorption (ν GAS ), thermal desorption (ν d ) and electron-induced precursor dissociation (ν el ):…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the effects of HS on metabolic parameters is presented in Table 1. 55, 58/ 1, 20, 27, 42, 43, 48, 53, 56, 57 1,10,11,26,42,47,48,53,56,57,48,61,63 a Adapted from (Sanders, 2010;Johnson, 2014;Pearce, 2014;Sanz-Fernandez, 2014;Abuajamieh, 2015) b Blood urea nitrogen c Non-esterified fatty acids 1 Abeni et al, 200722 Geraert et al, 199643 O'Brien et al, 20102 Achmadi et al, 1990 23 Habibian et al, 2014 44 Pearce et al, 2013a 3 Al-Harthi et al, 2012 24 Hall et al, 198045 Prunier et al, 19974 Alhidary et al, 201225 Hart et al, 198046 Rahimi, 20055 Angus et al, 200726 Itoh et al, 199847 Rhoads et al, 20096 Arad et al, 1983 27 Kamiya et al, 200648 Ronchi et al, 19997 Bell et al, 1989 28 Kanter, 195449 Sano et al, 19838 Bobek et al, 1997 29 Kappel et al, 199750 Sano et al, 19999 Boddicker et al, 2014 30 Lee and…”
Section: Effects Of Hs On Metabolismmentioning
confidence: 99%
“…This predisposes the GI tract to hypoxia, resulting in increased intestinal permeability, inflammation, and villus damage. Previous studies have demonstrated the use of dietary supplements including Zn Sanz-Fernandez et al, 2014;, glutamine (Lima et al, 2015), or betaine to improve intestinal integrity. A thorough description of nutritional alternatives is not within the scope of this article.…”
Section: Dietary Optionsmentioning
confidence: 99%